2009
DOI: 10.1364/oe.17.000947
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Raman-induced polarization pulling

Abstract: The interest towards passive control of the light polarization through nonlinear effects has been stimulated by recent works: in particular a polarization pulling effect has been obtained by means of stimulated Brillouin scattering. Here we investigate the condition for obtaining polarization pulling by exploiting the stimulated Raman scattering, which is most suitable for optical communications thanks to its large gain bandwidth. The role of the polarization-dependent Raman amplification and of the random fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 16 publications
5
70
0
Order By: Relevance
“…The similar result have been obtained in [9,11] by direct modeling of stochastic equations (4), viz. it was obtained that for the pump power P in < 10 W and PMD parameter D p >0.01 ps/km 1/2 SPM and XPM has no contribution to polarization pulling.…”
Section: > Replace This Line With Your Paper Identification Number (Dsupporting
confidence: 85%
See 2 more Smart Citations
“…The similar result have been obtained in [9,11] by direct modeling of stochastic equations (4), viz. it was obtained that for the pump power P in < 10 W and PMD parameter D p >0.01 ps/km 1/2 SPM and XPM has no contribution to polarization pulling.…”
Section: > Replace This Line With Your Paper Identification Number (Dsupporting
confidence: 85%
“…The new approach developed by Sergeyev et al [7,8] have shown that it is possible to simultaneously mitigate both PDG and PMD by using a fiber with a particular spin profile or, more specifically, a two-section fiber ('two-section approach') in which the first section has no spin and the second one is periodically spun. A new approach based on using anisotropy of Raman amplification (Raman polarizer) to repolarize and amplify signal rather than to depolarize it has been recently developed by Martinelli et al [9] , Kozlov et al [10] and Ursinini et al [11]. In this approach, arbitrary at the input, signal SOP with low input power is attracting to the pump SOP with high input power (polarization pulling) and so is stabilizing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently proposed in [1], the so-called Raman polarizers combine Raman amplification with the simultaneous repolarization of light. Namely, the outcoming signal beam is highly polarized, even in cases when the Raman polarizer is fed by unpolarized light.…”
mentioning
confidence: 99%
“…From the practical point of view, fiber optic Raman polarizers differ from typical Raman amplifiers in that a peculiar type of gain fiber should be selected. Namely, a Raman polarizer requires a low polarization mode dispersion (PMD) fiber, i.e., with PMD coefficients lower than 0.02 ps , see [1], [4], [5]. The lower the PMD coefficient, the greater the PDG, the better the performance of the Raman polarizer, the worse the RIN induced over the signal.…”
mentioning
confidence: 99%